2012
DOI: 10.1111/j.1523-1739.2011.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Test of the Effects of a Non‐Native Invasive Species on a Wintering Shorebird

Abstract: The abundance of nearly one-quarter of the world's shorebird species is declining. At the same time, the number of non-native species in coastal ecosystems is increasing rapidly. In some cases, non-native species may affect negatively the abundance and diversity of shorebird prey species. We conducted an experimental study of the effects of the introduced European green crab (Carcinus maenas) on prey consumption by wintering Dunlin (Calidris alpina) in a central California estuary. We placed green crabs and Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There is mixed evidence on the potential for adverse effects of a Green Crab invasion on other trophic levels. In an enclosure experiment, Estelle and Grosholz (2012) found that Green Crabs reduced polychaete consumption by Calidris alpina L. (Dunlin). Wong and Dowd (2014) modeled the effects of a Green Crab removal program on an intertidal sand flat and predicted that removal of 50% or 95% of Green Crabs from the food web would result in increased Pluvialis squatarola L. (Black-bellied Plover) biomass and increased removal of benthic prey by migrating shorebirds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is mixed evidence on the potential for adverse effects of a Green Crab invasion on other trophic levels. In an enclosure experiment, Estelle and Grosholz (2012) found that Green Crabs reduced polychaete consumption by Calidris alpina L. (Dunlin). Wong and Dowd (2014) modeled the effects of a Green Crab removal program on an intertidal sand flat and predicted that removal of 50% or 95% of Green Crabs from the food web would result in increased Pluvialis squatarola L. (Black-bellied Plover) biomass and increased removal of benthic prey by migrating shorebirds.…”
Section: Discussionmentioning
confidence: 99%
“…The Green Crab is an aggressive competitor, and may outcompete sympatric native crustaceans (Haarr and Rochette 2012, MacDonald et al 2007, McDonald et al 2001). It has a generalist diet, and has had negative effects on several invertebrate species, notably bivalves (DFO 2011, Klassen andLocke 2007), but also polychaetes (Estelle andGrosholz 2012, Gregory andQuijón 2011) and amphipods (Grosholz and Ruiz 1995). Green Crabs can destroy Zostera marina L. (Eelgrass) beds (DFO 2011, Garbary et al 2014, Neckles 2015, Matheson et al 2016, and their foraging behavior has the potential to affect shorebird prey consumption by altering the availability of benthic invertebrates (Estelle and Grosholz 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the last 50 years, nearly thirty percent (~ 3 billion) of the birds that underpin these ecosystem functions and services have been lost across all biomes within the U.S. and Canada alone (Rosenberg et al 2019). Further losses are predicted as an additional 30% of all bird species are exhibiting population declines, particularly shorebirds and waterbirds (Butchart et al 2010, Estelle and Grosholz 2012, Ceballos et al 2017, Rosenberg et al 2019. While many of these declines can be partly attributed to shrinking habitat availability following land conversions for agriculture and housing (Newton 2004, Kirby et al 2008, Stanton et al 2018, Díaz and Malhi 2022, it is becoming increasingly clear that population declines can be exacerbated by manipulations of the remaining habitat area.…”
Section: Introductionmentioning
confidence: 99%